2018
DOI: 10.1111/jdv.15142
|View full text |Cite
|
Sign up to set email alerts
|

Physician–patient communication and patient‐reported outcomes in the actinic keratosis treatment adherence initiative (AKTRAIN): a multicenter, prospective, real‐life study of treatment satisfaction, quality of life and adherence to topical field‐directed therapy for the treatment of actinic keratosis in Italy

Abstract: Communication clarity was associated with patient-reported outcomes and adherence beyond AK-related clinical parameters. Our study questions the current episodic approach to AK management and provides the rationale to develop chronic care models fostering patients' engagement and treatment alliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 31 publications
2
38
0
1
Order By: Relevance
“…[12,16] For many cases of AK, several treatment approaches are potentially suitable based on existing guidelines. This document therefore further complements existing guidelines and previous consensus papers by providing recommendations about selecting the appropriate Ingenol mebutate was one of the treatment options proposed for many of the profiles and this was driven by its association with good cosmetic outcomes [17,18] ; the predictable nature of the treatment and related short-term local skin reactions [19][20][21][22] ; and the fact that the administration regimen of ingenol mebutate allows for flexible use, as patients are able to decide how and when it is used according to their needs and individual condition. In a randomized, evaluator-blinded trial of ingenol mebutate 0.015% gel and diclofenac sodium 3% gel, patients experienced a shorter duration of skin reactions, with a peak after one week, with ingenol mebutate compared with diclofenac sodium, who experienced reactions throughout the 90-day treatment.…”
Section: Practical Recommendations For Application Of Topical Treatmentsmentioning
confidence: 89%
“…[12,16] For many cases of AK, several treatment approaches are potentially suitable based on existing guidelines. This document therefore further complements existing guidelines and previous consensus papers by providing recommendations about selecting the appropriate Ingenol mebutate was one of the treatment options proposed for many of the profiles and this was driven by its association with good cosmetic outcomes [17,18] ; the predictable nature of the treatment and related short-term local skin reactions [19][20][21][22] ; and the fact that the administration regimen of ingenol mebutate allows for flexible use, as patients are able to decide how and when it is used according to their needs and individual condition. In a randomized, evaluator-blinded trial of ingenol mebutate 0.015% gel and diclofenac sodium 3% gel, patients experienced a shorter duration of skin reactions, with a peak after one week, with ingenol mebutate compared with diclofenac sodium, who experienced reactions throughout the 90-day treatment.…”
Section: Practical Recommendations For Application Of Topical Treatmentsmentioning
confidence: 89%
“…Only four studies were clinical trials. 10,[23][24][25] Investigations were designed prevalently as national studies (10/14) 6,8,10,12,[15][16][17]22,23,26 and carried out in North America, 10,15 Europe, 8,16,17,22,26 South America, 6,23 and Australia. 12 Brazil was the only represented South American country, 6,23 and no data were present to represent Asian and African countries.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…6,22,24 5% to 57.9% of patients had a previous history of skin cancer, while 19.3% to 90.3% had been previously treated for AK. 6,8,10,12,13,[15][16][17]19,[22][23][24][25][26] The majority of the patients belonged to Fitzaptrick's skin phototypes I and II. In relation to satisfaction regarding the adverse effects, the group treated with DFS showed higher satisfaction compared to the group treated with 5-FU, with 93.3% and 38.4% of highly satisfied patients, respectively.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Discussing the treatment-associated local site reactions (LSRs) before therapy may lead to delay in treatment initiation. During treatment, such reactions cause distress [6] and impact health-related quality of life [7]. A study by Strohal et al [8] showed that 19.4% of patients treated with imiquimod 5% cream, scheduled unplanned visits due to their concern of LSRs.…”
Section: Introductionmentioning
confidence: 99%